Inclusão de alunos com deficiência visual nas aulas de Química: Estudo de caso acerca da concepção docente - Azevedo, Paulo Vidal Guanabara de (2020)
The conditions for developing methodologies in the teaching of chemistry may face challenges, regarding the process of inclusion of people with visual impairments. Thus, it is necessary that the chemistry teacher has a training that allows him to develop a pedagogical praxis, which favors the inclusion of these individuals. Thus, the present study raised the following question: How are chemistry teachers performing their duties in a common classroom with visually impaired students? Based on this questioning, this research has as main objective to investigate the conception of a chemistry teacher about the process of school inclusion of students with visual impairment. This research is presented as a case study carried out in a second-year class of high school that had four visually impaired students, in a state public school in the city of Campina Grande, Paraiba, Brazil. For data collection, we used a semi-structured interview and on-site observation. The analysis of the collected data was inspired by Laurence Bardin’s content analysis. The results showed that the chemistry teacher, object of the present investigation, understands the importance of the school inclusion of his students with visual impairment, as well as seeking to develop materials adapted to improve the teaching-learning process of these students. We also found that the evaluation processes applied, by the participant of the present investigation, did not verify the real learning of students with visual impairment. We emphasize that the mentioned teacher has limitations to develop materials adapted for students with visual impairment, due to the lack of specific training, in the scope of initial and continuing training, a high workload, as well as an absence of teaching assistants in the classroom. class. We conclude that the conception that the professor in study presents about the importance of a teaching practice that aims at the school inclusion of students with visual impairments was based on the right of these students to be in the classroom and to have access to the contents, but presented limitations regarding developing a pedagogical praxis that favors such access. The fact that the visually impaired student is in the classroom does not mean that the process of school inclusion is being carried out, just as the ineffectiveness of this process is not related to the absence of an inclusive practice by teachers, but to the Brazilian educational system that despite having built legislation, which guarantees access and permanence for students with disabilities in regular educational institutions, has shown a deficiency in the operationality of such a process.